Design manufacturing mesin pengaduk adonan roti - Catur Harsito; Ari Prasetyo; Teguh Triyono; Anugrah Akbar; Bimantoro Rachmawan Suseno; Eki Rovianto; Hammar Ilham Akbar (Institution for Industrial Research and Standardization of Industry - Padang, 2022)
Currently, bread is one of the alternative staple foods that is quite in demand by the public. This has resulted in the bread making industry being enthusiastically welcomed by business people because it has bright and open opportunities for large and small scales. However, the Micro, Small and Medium Enterprises (MSMEs) industry is unable to compete. One of them is because of the use of technology in the dough kneading process. This article discusses product planning for a horizontal type of bread dough mixer using the Design for Manufacturing and Assembly (DFMA) method and Quality Function Deployment (QFD) analysis where the design is based on design, materials, analysis, and equipment and manufacturing process planning. In this study, the Action Research method, engineering engineering and the Solidwork simulation design software were used. The design of the machine can be used for a stirring capacity of 10 kg and a rotation speed of 40 rpm. The results of the design consist of several main parts, namely the main frame, container, stirrer, motor, and transmission system